Peran Filantrophy Islam dalam Menanggulangi Kemiskinan - Salsabila Nafisa Nafisa; Naufal Kurniawan (Politeknik Baubau, 2023)
Poverty is a problem that always exists in every country, both in the form of absolute poverty and relative poverty. Efforts should be made to solve this problem of poverty, because if it cannot be resolved, it will become a problem that can disrupt economic activity. Poverty can be seen as a multidimensional problem because it is related to the inability to access economically, socially, culturally, politically and participate in society. Islamic philanthropy as a form of social generosity is directed to be able to answer the problem of poverty. There is Islamic philanthropy that is oriented towards poverty alleviation in the short term and long term, short term for example providing assistance that is consumptive and disposable. As for those that are long-term by providing assistance that can be used for a long time to increase income. The method used in this study is the library research model, where the author takes references from several books and journals in collecting data. The purpose of this research is to find out the role of Islamic philanthropy in alleviating poverty. Islamic philanthropy is expected to be a solution to economic problems in Indonesia in terms of poverty. Where income derived from the wages of a worker is one of the variables that can be used in poverty alleviation.